Peer Assisted Learning Program (PAL): A student-centric engagement tool for Foundation students - Romeo, Sharon; Krishna, Salomy Sumithra; Ilangovan , Sheila; Alvar, Thamilvaani Arvaree (International Journal of Psychosocial Rehabilitation, 2020)
The School of Foundation in Science at University of Nottingham Malaysia had observed a trend whereby students’ failure rate in Mathematics modules was 5-15% for every module offered each semester. As such, the Peer Assisted Learning (PAL) program was offered as a pilot program to provide learning support for students who needed to do the re-assessment examination. Prior to the implementation of the PAL program, a briefing and a survey were conducted to gauge students’ level of commitment towards the program. 94 % believed that the PAL program would increase their knowledge of the failed module. Students who had to re-sit the Mathematics modules were then encouraged to participate in the PAL program on a voluntary basis. Participants were assigned to student volunteer Mentors who had scored distinctions in their Maths modules. A minimum of 20 hours mentoring was required to be fulfilled by each of the Mentor-Mentee pair. In summary, the findings support much of the previous literature and case studies related to PAL programs. In addition, both PAL mentors and mentees perceived a number of benefits from the program. The re-assessment examination results also showed that the mentees outperformed their peers who prepared for the examination via self-study.